Cultural locations of disability - Snyder, Sharon L., 1963- (University of Chicago Press, 2006)
In Cultural Locations of Disability, Sharon L. Snyder and David T. Mitchell trace how disabled people came to be viewed as biologically deviant. The eugenics era pioneered techniques that managed "defectives" through the application of therapies, invasive case histories, and acute surveillance techniques, turning disabled persons into subjects for a readily available research pool. In its pursuit of normalization, eugenics implemented disability regulations that included charity systems, marriage laws, sterilization, institutionalization, and even extermination. Enacted in enclosed d.